CURRENT APPLICATIONS OF LASER IN CONSERVATIVE DENTISTRY AND ENDODONTICS. A SCOPING REVIEW. - Omar Ahmed Ghulam, Mousa Sulaiman Hazazi, Khalid Atif Sindi, Hasan Ahmad Taher, Ahmed Salah Alahmadi; Saleem Issam Albaradie, Somayah Sanad Al Rowaithi, Suhael Ahmed (Chelonian Research Foundation, 2024)
The use of lasers is considered an innovative method for clinical use in dentistry. Recently, multiple studies have been undertaken regarding the possible applications of laser therapy in dentistry. Furthermore, owing to their ablation, penetrability, and disinfection properties, lasers have excelled in conservative and endodontic procedures, encompassing root canal therapy, vital pulp therapy (pulp capping and pulpotomy), treatment of dentinal hypersensitivity, and management of dental pain associated with pulp and periradicular diseases. This study highlights the advantages of laser-assisted pulp therapy through summarized clinically controlled trials and histological investigations. Furthermore, the innovative application of lasers to enhance root development and facilitate the removal of foreign objects (such as fractured files and fiber posts) in canals has rapidly emerged as a leading trend in contemporary research. This review provides a synthesis and analysis of the existing literature on all the previously stated laser applications. Additionally, the attributes of laser devices, such as erbium lasers, neodymium-doped lasers, CO2 lasers, and diode lasers, are elucidated and examined here, offering valuable references for laser utilization in endodontics. We also concentrate on the various wavelengths pertaining to the lasers utilized in endodontics. High-power lasers function effectively as surgical tools; moreover, low-level lasers facilitate the modulation of pulp inflammation and enhance pulp healing. This narrative review summarizes the expanded applications of lasers alongside various devices in endodontics and seeks to inspire creative ideas on the use of lasers for treating dental disorders, particularly pulp diseases, in the future.